Infectious mononucleosis management in athletes - Ceraulo, A. S.; Bytomski, J. R. (Clinics in Sports Medicine, 2019)
Infectious mononucleosis is a common condition occurring in athletic training rooms. Most cases are due to Epstein-Barr virus infections (upward of 90%). Although treatment generally consists of symptomatic care, there is clinical variation in laboratory workup leading to diagnosis and in the method of return to play decision making. The authors suggest a systematic approach to laboratory evaluation and return to play decisions to minimize clinical variation. The most feared complication of infectious mononucleosis is potential splenic rupture. There have been several examples of the successful use of serial ultrasonography to help make maximally informed return to play decisions.